2018
DOI: 10.1038/s41395-018-0084-x
|View full text |Cite
|
Sign up to set email alerts
|

American College of Gastroenterology Monograph on Management of Irritable Bowel Syndrome

Abstract: IntroductionIrritable bowel syndrome (IBS) is the most prevalent of the functional gastrointestinal disorders (FGIDs). Current estimates are that IBS affects up to 10-12% of adults in North America (1,2). Although it can affect all individuals regardless of age, creed, or gender, IBS is more common among women and is most commonly diagnosed in younger individuals (< age 50) (2, 3). IBS is characterized by recurrent abdominal pain and altered bowel habits; bloating and distention frequently coexist. The diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
414
0
14

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 286 publications
(429 citation statements)
references
References 257 publications
(237 reference statements)
1
414
0
14
Order By: Relevance
“…In addition, a survey‐based study noted that 73% of 1094 individuals diagnosed with IBS‐D reported avoiding foods that they thought would cause stomach upset . The number needed to treat, or the number of patients needed for one patient to achieve improvement of symptoms with treatment (relative to control), is 5 for the low FODMAP diet compared with an alternative diet (n = 7 studies; quality of evidence was considered “very low”); the number needed to treat for a gluten‐free diet cannot be calculated accurately …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, a survey‐based study noted that 73% of 1094 individuals diagnosed with IBS‐D reported avoiding foods that they thought would cause stomach upset . The number needed to treat, or the number of patients needed for one patient to achieve improvement of symptoms with treatment (relative to control), is 5 for the low FODMAP diet compared with an alternative diet (n = 7 studies; quality of evidence was considered “very low”); the number needed to treat for a gluten‐free diet cannot be calculated accurately …”
Section: Resultsmentioning
confidence: 99%
“…The precise mechanism by which probiotics improve IBS symptoms is unknown; however, some patients may benefit from modulation of gut microbiota . A meta‐analysis of 37 randomised, controlled studies (n = 4403) reported that probiotics were significantly better than placebo for the improvement of IBS symptoms (relative risk of IBS not improving 0.81; 95% CI 0.74‐0.88) . Combination probiotic products were found to have significantly greater benefit than placebo (n = 21 randomised, controlled studies [1931 patients]; relative risk of IBS not improving, 0.79; 95% CI, 0.68‐0.91) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations